Theoretical perspectives for developing antiracist teaching dispositions and practices in preservice teacher education. Issue 5 (15th July 2022) - Madkins, Tia C.; Nazar, Christina Restrepo
Abstract: For some time, scholars who are guided by critical theories and perspectives have called out how white supremacist ideologies and systemic racism work to (re)produce societal inequities and educational injustices across science learning contexts in the United States. Given the sociopolitical nature of society, schooling, and science education, it is important to address the racist and settled history of scientific disciplines and science education. To this end, we take an antiracist stance on science teaching and learning and seek to disrupt forms of systemic racism in science classrooms. Since teachers do much of the daily work of transforming science education for minoritized learners, we advocate for preparing teachers who understand what it means to engage in antiracist, justice‐oriented science teaching. In this article, we share our framework for supporting preservice teachers in understanding, developing, and implementing antiracist teaching dispositions and instructional practices. In alignment with other researchers in teacher education who emphasize the importance of anchoring teacher education practice and research in prominent educational theory, we highlight the theories undergirding our approach to antiracist science teaching. We offer considerations for how researchers and science teacher educators can use this framework to transform science teacher education.